2016
DOI: 10.1108/apjba-09-2014-0106
|View full text |Cite
|
Sign up to set email alerts
|

The Big Five personality traits and burnout among Malaysian HR professionals

Abstract: Purpose – The purpose of this paper is to examine whether Malaysian HR professionals emotions regulation strategy mediates the relationship between their personality and burnout. To date few studies have examined such issues, especially among emerging Asian economies such as Malaysia. Design/methodology/approach – A model linking the Big Five personality to emotions regulation (deep and surface acting (SA)) and burnout was tested using d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 83 publications
(104 reference statements)
1
7
0
7
Order By: Relevance
“…On the other hand, skills-related issues such as "keeping up with technological changes, fear of obsolescence" were considered as factors contributing to burnout in IT (Pawlowski et al, 2007). Similar to our finding, in which, openness to experience has a negative effect on turnover intention, Santos et al (2016) found the significant effects of extroversion and openness to experience on work-related burnout among Malaysian human-resources professionals. Another study conducted by Agrawal et al (2012) concluded that IT professionals prefer not to work for longer periods on similar projects due to the "lack of growth and learning opportunities".…”
Section: Conclusion and Discussionsupporting
confidence: 87%
“…On the other hand, skills-related issues such as "keeping up with technological changes, fear of obsolescence" were considered as factors contributing to burnout in IT (Pawlowski et al, 2007). Similar to our finding, in which, openness to experience has a negative effect on turnover intention, Santos et al (2016) found the significant effects of extroversion and openness to experience on work-related burnout among Malaysian human-resources professionals. Another study conducted by Agrawal et al (2012) concluded that IT professionals prefer not to work for longer periods on similar projects due to the "lack of growth and learning opportunities".…”
Section: Conclusion and Discussionsupporting
confidence: 87%
“…To our knowledge there are only few studies investigating burnout among HR professionals (e.g. Santos et al, 2015;Santos et al, 2016;Mustafa et al, 2016;Mustafa et al, 2014), but only one focusing on recruiters (Prusik & Szulawski, 2019). The majority of burnout literature that include HR professionals deals with their practices used for preventing and reducing burnout of other employees (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These include both educators (Milfont, Denny, Ameratunga, Robinson, & Merry, 2008) and Malaysian human resources personnel (Santos, Mustafa, & Chern, 2016).…”
Section: Burnout In the Teaching Professionmentioning
confidence: 99%